A Randomised, Double-Blinded, Placebo-Controlled, Parallel Study of Vitamin D3 Supplementation with Different Schemes Based on Multiples of 25,000 IU Doses - Etienne Cavalier; Werner Faché; Jean-Claude Souberbielle (International Journal of Endocrinology)
Vitamin D (VTD) treatment is recommended in patients presenting different causes of diseases. To treat these patients, physicians rely on the different available pharmaceutical forms present in their country. Unfortunately, even in a given country, there is no consensus on the best way to treat the patients. In Belgium, VTD is mostly prescribed as ampoules containing 25,000 IU of VTD. In this randomised controlled study, we evaluated whether four therapeutic schemes using multiples of 25,000 IU of VTD according to basal vitamin D concentration were able to increase or maintain the 25(OH)D serum level above 30 ng/mL. We randomized 175 subjects who received the drug (n=140) or placebo (n=35). Total duration of the study was 12 weeks. Doses ranged from 4167 to 1667 IU/day. Blood sampling was performed at baseline and each 4 visits. In the treated (placebo) subjects, mean 25(OH)D serum concentration was 18.7 (19.1) ng/mL at baseline and 31.5 (20.7) ng/mL at w-12. At the end of the study, 57.1% of the subjects treated with VTD presented 25(OH)D serum concentration ≥30 ng/mL, whereas 94.3% were ≥20 ng/mL. In conclusion, the doses administered were safe and increased or maintained the 25(OH)D concentration ≥20 ng/mL. However, concentrations ≥30 ng/mL were only achieved in 57.1% of the subjects.